Uma análise da formação do professor de Geografia na UFU: limites e possibilidades - Costa, Lucemeire Da Silva (2003)
This study questions the commitment of the University with regard to the preservice Geography teacher. The used methodological approach is inspired by the thematic oral history. By oral narratives, which were transcribed and left in a textual form, of a group of ten educator teachers of the Geography Undergraduation Course of the Universidade Federal de Uberlândia, a reflection on the problem is made evidencing the Criticai Geography(ies) and the formation paradigms, that, traditionally, lie on the technical rationality, and on the emergent critical-reflexive model. The study reveals that the teacher's formation is procedural and compositing and that Geography has an important role on the citizenship formation. It also indicates the marginalization of the teaching in the academy, devoted by the lack of research activities and extensiop both related to the educational thematic in the Geography field. It is considered that there are many limits for the commitment but possible ways for an improvement of the educational process are revealed such as the professionafs formation while being critical-reflexive and investigative, the plural methodology, the elaboration and implementation of a pedagogic political project and a relationship narrowing among teaching, research and extension, in a way that a permanent and useful entailment is established between the university and the schools of fundamental and médium leveis.